Optimization of saccharification culture process and analysis of volatile flavor components of Qingchuan Huangjiu - REN Xiaohu, ZHU Ying, CHEN Lei, YANG Anting, GONG Hucheng, TIAN Shulin, BIAN Minghong, XU Qiang, HAN Baolin (Zhongguo niangzao)
In this study, using yellow, purple and white waxy corn as raw materials, Dazhu Xiaoqu, Huaxi Xiaoqu and Anqi sweet Jiuqu as starter culture, Qingchuan Huangjiu was prepared by different combinations of fermentation, and the most suitable fermentation raw materials and Jiuqu were determined. With alcohol content and sensory score as evaluation indexes, the optimum conditions for saccharification culture of Qingchuan Huangjiu were determined by single factor tests and Box-Benhnken response surface tests. The physicochemical indexes of Qingchuan Huangjiu were determined by national standard method, and the volatile flavor components were detected by GC-MS. The results showed that the optimal saccharification culture technology of Qingchuan Huangjiu was as follows: yellow waxy corn as raw material, Dazhu Xiaoqu as Jiuqu, Jiuqu addition 1.0%, saccharification culture temperature 28 ℃, time 61 h. The Qingchuan Huangjiu produced under these optimal conditions had harmonious taste, bright yellow color and rich aroma, with a unique style of Qingchuan Huangjiu, and the sensory score reached 93.6 points. The total acid (in terms of lactic acid), total sugar, amino acid nitrogen contents, alcohol content, and pH were (6.50±0.05) g/L, (7.86±0.04) g/L, (0.24±0.04) g/L, (12.50±0.21) %vol, and 3.65±0.054, respectively. The physicochemical indexes met the requirements of GB/T 13662—2018 "Huangjiu". A total of 28 volatile flavor substances were detected from Qingchuan Huangjiu, including 12 esters, 6 alcohols, 5 aldehydes, 4 acids and 1 ketone.